Corpus callosum morphology in children on mid-sagittal MR imaging - Raubenheimer, Lauren (Division of Radiology, 2019)
Background: There is little published research on the wide variation of corpus callosum (CC) morphology in children, the assessment of which is made difficult by the complex alteration of its appearance in childhood. Objective: The purpose of our study was to assess the morphology of the CC on mid-sagittal T1- weighted magnetic resonance imaging (MRI) in a large number of children and correlate the findings with demographic and clinical criteria. Materials and methods: We reviewed all brain mid-sagittal T1-weighted MRI’s performed from July to December 2015 and obtained relevant demographic and clinical information from the accompanying report and laboratory system. The CC morphology was analysed by three radiologists and compared using cross tabulation with the chi-square test and ANOVA. Interobserver correlation was assessed using Kappa coefficient of conformance. Results: 257 patients with mean age 72±60 months were included, 142 were male (55%). In abnormal MRI’s the CC was less likely to have an identifiable isthmus and was more likely to be convex, thin and have separation of the fornix insertion (all p<0.01). In young children (< 5 years) the CC was also less likely to have an identifiable isthmus (p=0.01) and was more likely to be convex (p=0.04) but the fornix was more likely to insert normally (p<0.01). Children with tuberous sclerosis had significantly thinner splenia (p=0.02). Conclusion: There is a distinct pathological appearance of the CC. The immature appearance of the corpus callosum can mirror this but is distinguished by normal insertion of the fornix and normal quantitative measurements. Splenial thinning in children with tuberous sclerosis warrants further investigation.